2019
DOI: 10.1111/cid.12761
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic peri‐implant outcomes of short dental implants placed in posterior jaws of patients with treated generalized aggressive periodontitis: A 3‐year follow‐up study

Abstract: Background: Studies assessing clinical and radiographic peri-implant parameters around short dental implants (SDIs) in treated generalized aggressive periodontitis (GAgP) patients are scant.Objectives: This 3-year follow-up study aimed to compare the clinical peri-implant and radiographic bone status around SDIs placed in partially edentulous patients treated for GAgP and periodontally healthy patients and to assess the implant success rate between both the groups. Materials and Methods:A total of seven patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Among these parameters, the individual susceptibility underlying the host response to the biofilm is considered important. Our results are in line with a previous study where a significantly higher incidence of implant loss was reported in patients with generalized aggressive periodontitis, compared with periodontally healthy patients (Akram et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Among these parameters, the individual susceptibility underlying the host response to the biofilm is considered important. Our results are in line with a previous study where a significantly higher incidence of implant loss was reported in patients with generalized aggressive periodontitis, compared with periodontally healthy patients (Akram et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…The success rate of short implants could be slightly lower than, higher than, or almost equal to the standard in previous studies. [11][12][13][14][15] Searching in a wide range of literature related to risk factors, 9,16 there was no consensus. In this retrospective study, we defined short implants as implant with an introbony length less than or equal to 8.5 mm according to some previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors indicate short implants as a predictable treatment option and a reasonable alternative to extensive regenerative procedures in patients with reduced volume of alveolar process [19,21,22]. According to Akram, short implants (< 6 mm) with 3 years of observation period were characterized by MBL of 0.42 mm in the first year of follow-up after loading, and significantly reduced to 0.14 mm in the following third year, as PD slightly reduced from 2.6 mm at the baseline to 2.4 mm at the third year of follow-up; however, CAL increased from 3.8 to 4.5 mm during this follow-up [23]. Dierens performed a retrospective study on total 50 implants and reported that 91.5% of the implants had a mean interproximal probing depth of < 5 mm with MBL at 1.7 mm after the first year of loading [24].…”
Section: Discussionmentioning
confidence: 94%